EFL Students’ Pragmatic Competence in writing: Request Strategies in Formal and Informal Letters - Trimadona, Eliza; Sulistiyo, Urip; Hadiyanto, Hadiyanto; Abrar, Mukhlash (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2026)
This study examines students’ pragmatic competence in using request strategies in English formal and informal letter writing, with particular attention to how learners adjust their linguistic choices according to context, social distance, and power relations. Adopting a qualitative case study design, the participants were twelve undergraduate EFL students who produced one formal and one informal letter containing request expressions. Data were collected through written tasks and supported by follow-up semi-structured interviews with selected participants to clarify pragmatic choices. The written data were analyzed based on Braun and Clarke’s six phases of thematic analysis, with NVivo software employed to support systematic coding and data organization. The analysis focused on patterns of request strategies to explore students’ contextual appropriateness in written communication. The findings indicate that students demonstrated emerging pragmatic competence by differentiating their use of request strategies across formal and informal contexts. In formal letters, students predominantly employed conventionally indirect strategies, particularly query preparatory forms, to show respect and avoid being too direct with institutional authority, although instances of excessive directness were still observed. In informal letters, however, flexibility, emotional expressiveness, and a wider combination of direct and indirect strategies were highlighted which reflected closer social relationships and reduced formality. The results suggest that students are developing their contextual awareness and politeness sensitivity, yet their pragmatic control remains uneven across communicative settings. The study offers the pedagogical importance of integrating explicit instruction on pragmatic features into EFL writing courses to support students’ ability to formulate contextually appropriate requests.